Pengetahuan dan Perilaku Sehat Masyarakat D.I Yogyakarta Terhadap Covid-19 Era Pandemi dan Endemi - Hidayah, Mudita Sri; Wardani, Wahyu Tusi (STIKes Surya Global Yogyakarta, 2024)
Background of Study: The President has declared the end of the Covid-19 pandemic status in Indonesia on June 21, 2023. This means that the Covid-19 pandemic status has ended and changed the factual status of Covid-19 to an endemic disease in Indonesia. Public attitudes have begun to not pay more attention to the pandemic and Covid-19 protocol that occurred in Indonesia. This study aims to describe knowledge and health behavior towards Covid-19 in the pandemic and endemic era. Methods: This study used an observational method with a cross sectional design. The study population was people who live in DI Province. Yogyakarta Province with purposive sampling. The research sample must meet the inclusion and exclusion criteria. Inclusion criteria in this study, namely people domiciled in Yogyakarta Province who are willing to fill out informed consent, aged 17 years and over and work in the non-health sector. Exclusion criteria in this study are people who live in DI Province. Yogyakarta Province who did not answer the questionnaire completely. Data analysis used is univariate analysis Results: The level of knowledge of the people of D. I Yogyakarta regarding Covid-19 in the pandemic and endemic era is quite good. 71.5% of respondents had a good level of knowledge about Covid-19 and experienced a decrease in healthy behavior in the endemic era compared to the pandemic period. Conclusion: The level of public knowledge related to Covid-19 in the pandemic and endemic era is quite good, but the healthy behavior of the community towards Covid-19 in the endemic era has decreased compared to during the pandemic. Keywords: Knowledge, Health Behavior, Covid-19, Pandemic, Endemic